2017
DOI: 10.1302/2046-3758.61.bjr-2016-0145.r1
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate fracture load of cadaver proximal humeri correlates more strongly with mean combined cortical thickness than with areal cortical index, DEXA density, or canal-to-calcar ratio

Abstract: ObjectivesThis investigation sought to advance the work published in our prior biomechanical study (Journal of Orthopaedic Research, 2016). We specifically sought to determine whether there are additional easy-to-measure parameters on plain radiographs of the proximal humerus that correlate more strongly with ultimate fracture load, and whether a parameter resembling the Dorr strength/quality characterisation of proximal femurs can be applied to humeri.Materials and MethodsA total of 33 adult humeri were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…Our results are in line with previous reports affirming that simple-to-measure radiographic parameters of the proximal humerus are more useful in predicting ultimate fracture load than sophisticated exams and evaluations such as DEXA density. [23] Combining our results with those of this article, we speculate that DEXA evaluations are not necessary for the diagnosis of osteoporosis of proximal humerus fractures.…”
Section: Accepted Manuscriptsupporting
confidence: 72%
“…Our results are in line with previous reports affirming that simple-to-measure radiographic parameters of the proximal humerus are more useful in predicting ultimate fracture load than sophisticated exams and evaluations such as DEXA density. [23] Combining our results with those of this article, we speculate that DEXA evaluations are not necessary for the diagnosis of osteoporosis of proximal humerus fractures.…”
Section: Accepted Manuscriptsupporting
confidence: 72%
“…These factors were also shown to be superior to other simple-to-measure radiographic parameters (areal cortical index, canal-to-calcar ratio, and medial cortical ratio) in determining bone strength. 13 Limitations of this study included the small sample size, which was due to the high costs associated with preparing cadaveric shoulder specimens, imaging preand post-fracture, and the process of cortical thickness mapping. A larger sample size would have increased the power of the study and reduced the risk of a type two error.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, only one type of parameter was used in most studies, either a numerical value or an index. 11 , 13 , 15 - 21 We found that the radiographic parameters of the distal femur, CBTavg and DFCI, correlated well with BMD and the T-score. Thus, these parameters could be used for identifying both osteoporosis and osteopenia.…”
Section: Discussionmentioning
confidence: 62%
“… 23 , 36 - 40 However, the relationship between the radiographic parameters and BMD have not been reappraised. 11 , 13 , 15 - 21 , 41 To our knowledge, this is the first study to propose new radiographic parameters focusing on the distal femur, where a fragility fracture has a high morbidity, 42 and compare these parameters with the BMD from DXA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation